MOBILE LEARNING TRANSFORMATION IN REDUCING EDUCATION DISPARITIES IN THE 3T REGION - Amar Marifat; Kristyan Dwijosusilo; Sri Roekminiati (International Journal of Multidisciplinary Reseach, 2026)
This study aims to evaluate the effectiveness of mobile learning in addressing educational challenges in Indonesia's Disadvantaged, Frontier, and Outermost (3T) regions, focusing on the use of the Kipin School 4.0 and Merdeka Mengajar platforms. 3T regions face various obstacles in obtaining quality education, primarily due to limited infrastructure and internet access. This study used a descriptive qualitative approach supported by semi-structured interviews and a quantitative survey involving teachers, students, and policymakers. Data analysis was conducted using a thematic approach and descriptive statistics, and used the SERVQUAL framework to assess the quality of digital education services. The results show that mobile learning can expand access to learning materials and help overcome geographical barriers and technological limitations. The Kipin School 4.0 and Merdeka Mengajar platforms have proven effective even in areas with limited connectivity. Assessment using the SERVQUAL method showed high levels of reliability, responsiveness, and accessibility. However, challenges remain, such as the lack of supporting infrastructure and the need for digital training for educators. Thus, mobile learning has significant potential to improve access and equity in education in the 3T (third-to-third) regions, although its long-term success depends heavily on strengthening infrastructure and providing sustainable digital training. Further research is needed to assess the long-term impacts and the feasibility of implementing hybrid education models in the future.